Enhancing students' conceptual understanding of trigonometric functions through geogebra-based learning - Juandi, Juandi; Sugiatno, Sugiatno; Noviani, Evi (Al-Jabar: Jurnal Pendidikan Matematika, 2025)
Purpose: This study explores how students construct basic trigonometric function definitions using GeoGebra, examines their engagement, and identifies the challenges they face. The research follows a constructivist approach, emphasizing active learning through technology to improve students’ understanding of mathematical concepts.Method: A pedagogical action research method was used, involving four stages: observation, planning, action, and reflection. The study was conducted with 31 Grade X science students from SMA Negeri 1 Sungai Kakap, selected through purposive sampling. Data were collected through observations, questionnaires, and interviews to assess the effectiveness of the GeoGebra-based learning approach.Findings: The results show that students successfully built definitions of basic trigonometric functions, achieving an average score of 95.24 percent, classified as "Very Good." Additionally, students responded positively to GeoGebra-based learning, with an average satisfaction score of 83.68 percent. However, some students faced technical difficulties, such as unstable internet connections and challenges in navigating the Geogebra application. Despite these issues, the approach proved effective in supporting interactive and engaging learning.Significance: This study highlights the benefits of using GeoGebra to enhance students’ understanding of trigonometric concepts through a constructivist learning approach. The findings suggest that improving infrastructure, providing training in technology use, and offering active teacher support can help maximize the impact of technology in mathematics education. These insights contribute to the ongoing development of digital learning strategies in secondary school mathematics.